The Semiotics of Pamali: Indigenous Character Education in the Makassar-Gowa Community - Sulastri, Sulastri; Ratnawati, Ratnawati; Abdollah, Abdollah; Watri, Luthfiah Nurhuda; Syukur, Hakan (Perkumpulan Program Studi Doktor Pendidikan (PPSDP), 2025)
This study employs Roland Barthes’ semiotic framework to analyze the types and layered meanings of Pamali (cultural taboos) within the Makassar-Gowa community of Indonesia. Using a case study with a descriptive qualitative design, data were collected through interviews, field observations, and document analysis. The findings revealed five categories of Pamali: Bad-Luck/Fortune, Sacred-Place, Manners & Social-Ethics, Attitudinal, and Religious/Time-Bound. Barthesian analysis demonstrates that these prohibitions operate at denotative (literal prohibition), connotative (moral/cultural value), and mythic (ideological) levels, functioning as an indigenous system of character education. The study concludes that Pamali was a dynamic semiotic pedagogy, transmitting values of respect, responsibility, and social harmony. This research offers a model for integrating local wisdom into culturally responsive education curricula.